Parent and perinatal professional priorities and perspectives for the pre-birth periviable conversation: a thematic analysis of semi-structured interviews - Peterson, J.; Johnstone, E. J.; Mahaveer, A.; Smith, D. M. (Frontiers in Pediatrics, 2025)
BackgroundPeriviable birth (22 + 0–23 + 6 weeks) presents clinicians and parents with numerous ethical, psychological and practical difficulties. The study aimed to identify key features within pre-birth periviable conversations for both professionals and parents, including priorities and challenges.MethodsSemi-structured interviews were conducted with participants from the key stakeholder groups: neonatologists/paediatricians (n = 5), obstetricians (n = 5), midwives (n = 5) and parents (n = 7). Interviews explored their experience of periviable counselling including priorities, challenges and perceptions. Thematic analysis was used to develop across parents and professionals.ResultsThree themes were identified summarising the parent and professional perspectives within the pre-birth periviable conversations: chronology and narrative within pre-birth conversations, different perspectives on uncertainty and the role of transparency within periviable trauma. The trauma experienced by parents through periviable birth can be compounded through poor communication practices of perinatal professionals. These themes demonstrate that the information provided to parents should consistently outline all available care options relevant to their baby, including compassionately delivered, but honest and descriptive accounts of emotive options, such as comfort care. Information should be individualised to the specific circumstances and risk factors of that individual family and incorporate discussion of topics key to the ‘good parent belief’ to empower parents within their role.ConclusionPerinatal professionals need to be able to utilise transparent communication, individualisation of information and understand the necessary role that narrative plays within decision-making. Future research is required to better understand the educational methods best suited to train perinatal professionals to incorporate these, and other trauma-informed care principles, within their communication and interactions with future parents.